Hubungan Antara Pengetahuan Dan Sikap Dengan Perilaku Sadari Pada Mahasiswi Stik Muhammadiyah Pontianak - Lukita, Yenny (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2014)
Research Background: Early detection of breast cancer is an essential thing to prevent the incidence of breast cancer in late stage. Practicing Breast Self Examination (BSE) is recommended for early detection of breast cancer. The underlying of behavior is knowledge and attitude. Nursing student should already know the importance doing of breast self examination (BSE) as early detection of breast cancer, but in fact most of the student is not doing breast self examination (BSE). Research Objective: To knew correlation between knowledge with attitude of breast self examination and to know correlation between attitude with behavior breast self examination. Research Method: The type of the reseach is descriptive analytic. The reseach was performed in STIK Muhammadiyah Pontianak. The sample in this reseach is 154 respondents. Accumulation data use questionnaire with Guttman scale. Univariate analysis using the percentage of variable knowledge, attitude, and behavior. Bivariate analysis using Chi Square with the significance ?=0.05. Research Result: The result of reseach that majority of them has good knowledge on breast self examination (55,2%), majority of them had supportive attitude on breast self examination (51,3%), and majority of them had positive behavior (51,9%). Conclusion: There was a significant correlation between knowledge with attitude of breast self examination. There was a significant correlation between attitude with behavior breast self examination.